A kind of iron disulfide / titanium dioxide microrod composite material and its preparation method and application

The iron disulfide/titanium dioxide microrod composite material was prepared through hydrothermal reaction, which solved the high volume effect and polysulfide shuttle effect of iron disulfide negative electrode material in potassium ion batteries, and achieved the high rate performance and electrochemical stability of the material , significantly improves the electrochemical performance of potassium ion batteries.

CN118929774BActive Publication Date: 2024-12-31SHENZHEN HONGZHUAN INTELLECTUAL PROPERTY MANAGEMENT SERVICE CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411419860.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-31
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The iron disulfide negative electrode material in existing potassium ion batteries has caused the shedding of active substances and the attenuation of potassium storage capacity due to the high volume effect and polysulfide shuttle effect, which cannot effectively solve the bottleneck of iron disulfide in potassium ion batteries.

Method used

Titanium glycerate microrods were prepared by hydrothermal reaction and mixed with iron salt and anhydrous ethanol. The iron salt was recrystallized and pyrolyzed on the titanium dioxide nanosheets by heat treatment to form highly dispersed iron disulfide nanoparticles combined with titanium dioxide nanosheets. Cross structure, providing effective space and pores, enhancing the electrochemical properties of the material.

Benefits of technology

The rate performance and electrochemical cycle stability of iron disulfide/titanium dioxide microrod composite materials are improved, and the high reversible specific capacity and capacity retention rate are maintained, which significantly improves the electrochemical performance of potassium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118929774B_ABST
    Figure CN118929774B_ABST
Patent Text Reader

Abstract

The invention discloses an iron disulfide / titanium dioxide microrod composite material and a preparation method and application thereof, and relates to the technical field of potassium ion batteries. The iron disulfide / titanium dioxide microrod composite material prepared by the invention comprises microrods formed by cross-section of titanium dioxide nanosheets and iron disulfide nanoparticles highly dispersed on the titanium dioxide nanosheets. Titanium glycerate microrods are prepared by hydrothermal reaction, and then mixed and stirred with iron salt and anhydrous ethanol, and the iron salt is pyrolyzed in situ by heat treatment, and then sulfur powder is added to react to obtain a composite material. The invention utilizes the large space formed by the interlacing of titanium dioxide nanosheets, the polar adsorption characteristics of titanium dioxide nanosheets for polysulfide, and the highly dispersed small particles of iron disulfide, so that when it is used as the negative electrode material of potassium ion batteries, it can effectively avoid the high volume effect and the polysulfide shuttle effect, thereby showing potassium storage performance, rate performance and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of potassium ion batteries, and in particular to an iron disulfide / titanium dioxide microrod composite material and a preparation method and application thereof. Background Art

[0002] With the dual carbon goals proposed, the development of high-performance energy storage devices is one of the key technologies for the efficient integration of renewable energy. Potassium-ion batteries, as a new type of energy storage device, have received extensive attention and research in recent years due to their low cost and fast potassium ion transmission rate. At present, the bottleneck restricting the development of potassium-ion batteries mainly lies in the development of a high-performance potassium storage negative electrode material.

[0003] Among the numerous potassium ion negative electrode materials, transition metal sulfides such as iron disulfide FeS2 have become one of the best candidates for potassium ion battery negative electrode materials due to their low cost and high theoretical capacity. However, iron disulfide negative electrodes exhibit poor electrochemical performance in the actual potassium storage process. The reasons are: (1) high volume effect, that is, the larger ionic radius of potassium ions causes iron disulfide to induce a huge volume expansion during the potassium insertion process, causing the iron disulfide active material to fall off the current collector; (2) polysulfide shuttle effect, that is, iron disulfide will produce polysulfides during the process of potassium ion insertion and extraction. The polysulfides are prone to shuttle effect in the electrolyte and cause rapid attenuation of potassium storage capacity. These problems seriously hinder the continued application of iron disulfide in the field of potassium ion batteries. Therefore, it is necessary to prepare a material that can meet the requirements of potassium ion battery negative electrode materials based on iron disulfide.

[0004] In the prior art, CN113578351A discloses pyrite / titanium dioxide composite material and its preparation method and application, wherein, the method for preparing FeS2 / TiO2 composite material mainly includes: hydrothermal method, solvent thermal method, sol-gel method, magnetron sputtering-sulfurization method, electrostatic spinning method, direct mixing, etc., but the above method has the problems of secondary pollution and complicated preparation process, and the above patent adopts iron powder, sulfur powder, titanium dioxide powder and grinding aid to obtain composite material after ball milling, and the above method reduces the particle size of FeS2 by the introduction of TiO2, so that the particle size of composite material is 10-50nm, and realizes Fe and S element doping into TiO2 lattice structure to a certain extent by ball milling, thereby improving material performance. But adopting the simple physical mixing method of ball milling, it is still impossible to achieve uniform distribution of FeS2 and TiO2 components. In addition, it can be seen from the electron microscope image that the internal pores are very small. Since the radius of potassium ions is larger than that of lithium ions, and the volume expansion of iron disulfide when used as a potassium ion battery material is much greater than that of lithium ion batteries, the iron disulfide / titanium dioxide composite material obtained by the above patent still cannot solve the problem of the iron disulfide active substance falling off from the current collector when used as a potassium ion battery material.

[0005] Therefore, there is an urgent need to prepare an iron disulfide material to solve the defects of high volume effect and polysulfide shuttle effect when it is used as a negative electrode material for potassium ion batteries. Summary of the invention

[0006] In view of the above-mentioned prior art, the purpose of the present invention is to provide an iron disulfide / titanium dioxide microrod composite material and its preparation method and application. The present invention prepares titanium glycerate microrods by hydrothermal reaction, and then mixes and stirs the titanium glycerate microrods with iron salt and anhydrous ethanol, and utilizes the volatilization of anhydrous ethanol to allow the iron salt to recrystallize on the titanium glycerate nanosheets, and then heat-treats the iron salt to in-situ pyrolyze on the surface of the titanium dioxide nanosheets to obtain Fe2O3 nanoparticles, and then adds sulfur powder to react to obtain iron disulfide nanoparticles dispersed on the titanium dioxide nanosheets. In the composite material prepared by the present invention, iron disulfide nanoparticles with potassium intercalation activity are highly dispersed on the surface of titanium dioxide nanosheets, and the titanium dioxide nanosheets are crossed to form a micron rod structure. The micron rod structure provides an effective space for the volume change of the iron disulfide active material when it is deintercalated / intercalated with potassium ions, thereby increasing the contact area between the iron disulfide active material and the electrolyte, thereby improving its rate performance. The present invention also utilizes the polar adsorption effect of titanium dioxide to adsorb polysulfides generated during the reaction, thereby preventing the polysulfides from having a shuttle effect in the electrolyte, so as to improve the electrochemical cycle stability of the material.

[0007] To achieve the above object, the present invention adopts the following technical solution:

[0008] The first aspect of the present invention provides a method for preparing an iron disulfide / titanium dioxide microrod composite material, comprising the following steps:

[0009] (1) Ethylene glycol and glycerol are mixed to obtain a mixed solution, a titanium source is added to the mixed solution for reaction, and after the reaction is completed, a precipitate is collected, washed, and dried to obtain glyceric acid titanium microrods;

[0010] (2) dispersing titanium glycerate microrods in anhydrous ethanol, adding iron salt, and stirring until the anhydrous ethanol evaporates to obtain iron salt / titanium glycerate microrods;

[0011] (3) heat treating the iron salt / titanium glycerate microrods to obtain iron oxide / titanium dioxide microrods;

[0012] (4) The ferric oxide / titanium dioxide microrods are mixed with sulfur powder to obtain a mixture, and the mixture is heat treated to obtain an ferric disulfide / titanium dioxide microrod composite material.

[0013] Preferably, in step (1), the volume ratio of ethylene glycol to glycerol in the mixed solution is (3-8):1.

[0014] Preferably, in step (1), the titanium source is one of titanyl sulfate, tetrabutyl titanate, titanium tetrachloride, and titanium isopropoxide.

[0015] Preferably, in step (1), the solid-liquid ratio of the titanium source to the mixed solution is (1-5) mmol:60 mL.

[0016] Preferably, in step (1), the reaction temperature is 120-200° C. and the reaction time is 10-18 h.

[0017] Preferably, in step (2), the iron salt is one of ferric nitrate nonahydrate, ferric carbonate, ferrocene, ferric sulfate, and ferric sulfate heptahydrate.

[0018] Preferably, in step (2), the ratio of the added amount of titanium glycerate microrods and iron salt is 0.2 g: (1-3) mmol.

[0019] Preferably, in step (2), the material-liquid ratio of titanium glycerate microrods to anhydrous ethanol is 0.2 g: (30-60) mL.

[0020] Preferably, in step (3), the heat treatment conditions are: heating to 300-600°C at a heating rate of 2-10°C / min, and keeping the temperature for 0.5-4h.

[0021] Preferably, in step (4), the mass ratio of ferric oxide / titanium dioxide microrods to sulfur powder is 1:(1-10).

[0022] Preferably, in step (4), the heat treatment operation is: placing the mixture in an argon atmosphere, heating the mixture to 400-600° C. at a heating rate of 2-10° C. / min, and maintaining the temperature for 1-4 h.

[0023] The second aspect of the present invention provides an iron disulfide / titanium dioxide microrod composite material.

[0024] Preferably, the iron disulfide / titanium dioxide microrod composite material is composed of titanium dioxide microrods and iron disulfide nanoparticles, the iron disulfide nanoparticles are dispersed on the surface of the titanium dioxide microrods, and the titanium dioxide microrods are composed of titanium dioxide nanosheets.

[0025] Further preferably, the size of the iron disulfide nanoparticles is 15-40 nm, and the thickness of the titanium dioxide nanosheets is 40-80 nm.

[0026] The third aspect of the present invention provides the use of the iron disulfide / titanium dioxide microrod composite material in the preparation of anode materials for potassium ion batteries.

[0027] Preferably, the potassium ion battery negative electrode material is prepared by the following method:

[0028] The iron disulfide / titanium dioxide microrod composite material, acetylene black and potassium carboxymethyl cellulose are mixed and dissolved in water to obtain a mixture, and the mixture is coated on a copper foil and dried to obtain a potassium ion battery negative electrode material.

[0029] Further preferably, the mass ratio of the iron disulfide / titanium dioxide microrod composite material, acetylene black and potassium carboxymethyl cellulose is 8:1:1.

[0030] More preferably, the thickness of the copper foil is 25 μm.

[0031] More preferably, the drying temperature is 80° C. and the drying time is 12 h.

[0032] Beneficial effects of the present invention:

[0033] The present invention prepares glyceric acid titanium microrods through a hydrothermal reaction, and then mixes and stirs the glyceric acid titanium microrods with iron salt and anhydrous ethanol, and utilizes the volatilization of the anhydrous ethanol to allow the iron salt to recrystallize on the glyceric acid titanium nanosheets, and then utilizes heat treatment to in-situ pyrolyze the iron salt on the surface of the titanium dioxide nanosheets to obtain Fe2O3 nanoparticles, and then adds sulfur powder to react to obtain iron disulfide nanoparticles dispersed on the titanium dioxide nanosheets.

[0034] The iron disulfide / titanium dioxide microrod composite material prepared by the present invention includes microrods composed of titanium dioxide nanosheets and iron disulfide nanoparticles highly dispersed on the titanium dioxide nanosheets, and the iron disulfide particles have a size of 15-40 nm. When the titanium dioxide nanosheets cross each other to form a microrod structure, there are a large number of pores, which provide an effective space for the volume change of the iron disulfide active substance when it is de- / embedded with potassium ions, and the pores can also make the electrolyte infiltrate in the iron disulfide / titanium dioxide microrod composite material, increase the contact area between the iron disulfide active substance and the electrolyte, thereby shortening the diffusion path of potassium ions, thereby improving the rate performance of the composite material. In addition, titanium dioxide, as a polar substance, can effectively adsorb the potassium polysulfide intermediate product formed when iron disulfide is de- / embedded with potassium ions, prevent potassium polysulfide from shuttling in the electrolyte, thereby improving the electrochemical cycle stability of the composite material. Thanks to the structural uniqueness of the composite material, when used as a potassium ion negative electrode material, it exhibits excellent electrochemical stability and rate performance.

[0035] In the ferric oxide / titanium dioxide microrod composite material prepared by the present invention, titanium dioxide nanosheets are intertwined to form a large space, the titanium dioxide nanosheets have the polarity to adsorb polysulfide characteristics, and the iron disulfide particle size is very small. Through the direct synergistic effect of the above three aspects, the ferric oxide / titanium dioxide microrod composite material exhibits excellent potassium storage performance when used as a negative electrode material for a potassium ion battery. When the charge and discharge current density is 0.1A / g, the reversible specific capacity is maintained at 544.9mAh / g after 100 cycles, and the capacity retention rate is as high as 89.9%; when the charge and discharge current is increased to 5A / g, the high reversible specific capacity of 422.4mAh / g is still maintained. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 : Scanning electron microscope image of the iron disulfide / titanium dioxide microrod composite material obtained in Example 4;

[0037] Figure 2 : XRD pattern of the iron sulfide / titanium dioxide microrod composite material prepared in Example 4;

[0038] Figure 3 : Electrochemical cycle life test diagram of the iron disulfide / titanium dioxide microrod composite material prepared in Example 4 and Comparative Example 1;

[0039] Figure 4 : Electrochemical rate performance test diagram of the iron disulfide / titanium dioxide microrod composite material prepared in Example 4 and Comparative Example 1. DETAILED DESCRIPTION

[0040] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0041] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0042] At present, iron disulfide can be used as an ideal material for the negative electrode of potassium ion batteries due to its low cost and high theoretical capacity. However, when it is used as the negative electrode material of potassium ion batteries, due to the high volume effect and polysulfide shuttle effect, the active material falls off the current collector and the sulfur element is lost, resulting in a rapid decay of the potassium storage capacity, which in turn affects the application of iron disulfide in the battery field.

[0043] Based on this, the present invention provides an iron disulfide-titanium dioxide microrod composite material and its preparation method and application. The preparation method of the iron disulfide-titanium dioxide microrod composite material is as follows: firstly, glycerol, ethylene glycol and a titanium source are subjected to a hydrothermal reaction to obtain glyceric acid titanium microrods, which are then dispersed in anhydrous ethanol, iron salt is added and stirred until the anhydrous ethanol is volatilized to obtain iron salt / glyceric acid titanium microrods, which are subjected to heat treatment to obtain iron trioxide / titanium dioxide microrods, which are then subjected to heat treatment after adding sulfur powder to obtain the final product.

[0044] In the above preparation process, hydrothermal reaction is used to prepare titanium glycerate with a micro-rod structure composed of nanosheets intersecting each other, and then the iron salt is recrystallized on the surface of the titanium glycerate nanosheet by volatilization of anhydrous ethanol. Then, during the heat treatment process, the titanium glycerate nanosheet is transformed into titanium dioxide nanosheet, and the iron salt is in situ pyrolyzed on the surface of the titanium dioxide nanosheet to generate iron trioxide particles. This in situ pyrolysis allows the iron trioxide particles to be highly dispersed on the surface of the titanium dioxide nanosheet, effectively preventing the agglomeration of the iron trioxide nanoparticles, which provides a basis for the subsequent sulfurization to form iron disulfide particles highly dispersed on the surface of the titanium dioxide nanosheet.

[0045] The iron disulfide / titanium dioxide microrod composite material prepared by the present invention comprises a titanium dioxide carrier and iron disulfide nanoparticles, wherein the titanium dioxide carrier is a microrod composed of nanosheets interlaced with each other, and the nanosheets are interlaced with each other to form large pores, which, on the one hand, provide sufficient space for the volume change of iron disulfide during potassium removal / intercalation, and on the other hand, are also conducive to the flow of electrolyte in the composite material, increase the contact between the iron disulfide active material and the electrolyte, thereby shortening the potassium ion diffusion distance, thereby simultaneously improving the cycle performance and rate performance when used as a negative electrode material for potassium ion batteries. At the same time, the titanium dioxide nanosheets have a polar adsorption effect, and can polarly adsorb polysulfides generated by iron disulfide during potassium removal / intercalation, prevent the occurrence of the shuttle effect of polysulfides in the electrolyte, thereby improving the cycle stability performance when used as a negative electrode material for potassium ion batteries. At the same time, the iron disulfide nanoparticles, which serve as the main potassium storage body, have a very small particle size, which can not only alleviate the volume expansion of iron disulfide during the process of potassium extraction / insertion and shorten the diffusion path of ions / electrons, but also greatly introduce surface pseudocapacitive potassium storage characteristics, thereby effectively improving the cycle and rate performance when used as a negative electrode material for potassium ion batteries.

[0046] The experimental materials used in the embodiments of the present invention are all conventional experimental materials in the art and can be purchased through commercial channels.

[0047] Among them, titanyl sulfate (99%), tetrabutyl titanate (99%), glycerol (99.5%) and ethylene glycol (98%) were purchased from Aladdin, titanium isopropoxide (97%) and ferric nitrate nonahydrate (99.9%) were purchased from McLean, and sulfur powder (99.5%) was purchased from China National Pharmaceutical Group.

[0048] Example 1: Preparation of Iron Disulfide / Titanium Dioxide Microrod Composite Material

[0049] (1) Ethylene glycol and glycerol were mixed in a volume ratio of 5:1 to obtain a mixed solution, 2 mmol of tetrabutyl titanate was added to 60 mL of the mixed solution and stirred, and the mixture was reacted at 120° C. for 12 h. After the reaction was completed, the precipitate was collected, washed, and dried to obtain glycerol titanium microrods;

[0050] (2) Disperse 0.2 g of titanium glycerate microrods into 40 mL of anhydrous ethanol, add 2 mmol of ferric nitrate nonahydrate, and stir until the anhydrous ethanol evaporates to obtain iron salt / titanium glycerate microrods;

[0051] (3) placing the iron salt / titanium glycerate microrods in a muffle furnace and heating the temperature to 500°C at a heating rate of 5°C / min, and keeping the temperature for 1 hour to obtain ferric oxide / titanium dioxide microrods;

[0052] (4) After mixing 0.1 g of ferric oxide / titanium dioxide microrods with 0.5 g of sulfur powder to obtain a mixture, the mixture was placed in a tubular furnace and heated to 550°C at a heating rate of 5°C / min under an argon atmosphere. The mixture was kept warm for 2 h to obtain an iron disulfide / titanium dioxide microrod composite material.

[0053] Example 2: Preparation of Iron Disulfide / Titanium Dioxide Microrod Composite Material

[0054] (1) Ethylene glycol and glycerol were mixed in a volume ratio of 5:1 to obtain a mixed solution, 2 mmol of titanyl sulfate was added to 60 mL of the mixed solution and stirred, and the mixture was reacted at 120° C. for 18 h. After the reaction was completed, the precipitate was collected, washed, and dried to obtain glycerol titanium microrods;

[0055] (2) Disperse 0.2 g of titanium glycerate microrods into 50 mL of anhydrous ethanol, add 2 mmol of ferric nitrate nonahydrate, and stir until the anhydrous ethanol is completely evaporated to obtain iron salt / titanium glycerate microrods;

[0056] (3) placing the iron salt / titanium glycerate microrods in a muffle furnace and heating the temperature to 550°C at a heating rate of 3°C / min, and keeping the temperature for 4 hours to obtain ferric oxide / titanium dioxide microrods;

[0057] (4) After mixing 0.1 g of ferric oxide / titanium dioxide microrods with 0.8 g of sulfur powder to obtain a mixture, the mixture was placed in a tubular furnace, and heated to 450°C at a heating rate of 5°C / min under an argon atmosphere, and kept warm for 2 h to obtain an iron disulfide / titanium dioxide microrod composite material.

[0058] Example 3: Preparation of Iron Disulfide / Titanium Dioxide Microrod Composite Material

[0059] (1) Ethylene glycol and glycerol were mixed in a volume ratio of 5:1 to obtain a mixed solution, 2 mmol of titanium isopropoxide was added to 60 mL of the mixed solution, stirred, and reacted at 150° C. for 14 h. After the reaction was completed, the precipitate was collected, washed, and dried to obtain titanium glycerate microrods;

[0060] (2) Disperse 0.2 g of titanium glycerate microrods into 60 mL of anhydrous ethanol, add 2 mmol of ferric nitrate nonahydrate, and stir until the anhydrous ethanol is completely evaporated to obtain iron salt / titanium glycerate microrods;

[0061] (3) placing the iron salt / titanium glycerate microrods in a muffle furnace and heating the temperature to 500°C at a heating rate of 5°C / min, and keeping the temperature for 3 hours to obtain ferric oxide / titanium dioxide microrods;

[0062] (4) After mixing 0.1 g of ferric oxide / titanium dioxide microrods with 1.0 g of sulfur powder to obtain a mixture, the mixture was placed in a tubular furnace and heated to 550°C at a heating rate of 5°C / min under an argon atmosphere and kept warm for 2 h to obtain an iron disulfide / titanium dioxide microrod composite material.

[0063] Example 4: Preparation of Iron Disulfide / Titanium Dioxide Microrod Composite Material

[0064] (1) Ethylene glycol and glycerol were mixed in a volume ratio of 5:1 to obtain a mixed solution, 2 mmol of titanium isopropoxide was added to 60 mL of the mixed solution, and stirred, and reacted at 180°C for 18 h. After the reaction was completed, the precipitate was collected, washed, and dried to obtain titanium glycerate microrods;

[0065] (2) Disperse 0.2 g of titanium glycerate microrods into 40 mL of anhydrous ethanol, add 2 mmol of ferric nitrate nonahydrate, and stir until the anhydrous ethanol is completely evaporated to obtain iron salt / titanium glycerate microrods;

[0066] (3) placing the iron salt / titanium glycerate microrods in a muffle furnace and heating the temperature to 400°C at a heating rate of 2°C / min, and keeping the temperature for 3 hours to obtain ferric oxide / titanium dioxide microrods;

[0067] (4) After mixing 0.1 g of ferric oxide / titanium dioxide microrods with 0.5 g of sulfur powder to obtain a mixture, the mixture was placed in a tubular furnace, heated to 500 °C at a heating rate of 2 °C / min under an argon atmosphere, and kept warm for 2 h to obtain an iron disulfide / titanium dioxide microrod composite material.

[0068] The structure of the iron disulfide / titanium dioxide microrod composite material prepared in this example was characterized. Figure 1-Figure 2 shown.

[0069] Depend on Figure 1 It can be seen that the morphology of the iron disulfide / titanium dioxide microrod composite material obtained in this embodiment is a micron rod assembled by titanium dioxide nanosheets with iron disulfide nanoparticles on the surface, wherein iron disulfide has a very small particle size as a potassium storage active material, which not only reduces the volume change of iron disulfide and shortens the diffusion distance of potassium ions, but also the small particle size can greatly introduce the surface pseudocapacitive potassium storage characteristics, which is beneficial to the rate performance as a potassium ion negative electrode material. Titanium dioxide nanosheets as carriers of iron disulfide particles cross each other to form a large number of pores, which is beneficial to alleviate the volume expansion of iron disulfide particles when de- / embedded potassium ions, and on the other hand, it is also beneficial to the flow of electrolyte in the composite material, increasing the contact between the iron disulfide active material and the electrolyte to shorten the diffusion distance of potassium ions.

[0070] Depend on Figure 2 It can be seen that the XRD spectrum of the iron disulfide / titanium dioxide microrod composite material prepared in this example is consistent with the standard PDF card of iron disulfide (JCPDF NO.42-1340) and the standard PDF card of titanium dioxide (JCPDFNO.21-1272), respectively, proving that the composite material is composed of iron disulfide and titanium dioxide.

[0071] Example 5: Preparation of Iron Disulfide / Titanium Dioxide Microrod Composite Material

[0072] (1) Ethylene glycol and glycerol were mixed in a volume ratio of 3:1 to obtain a mixed solution, 1 mmol of tetrabutyl titanate was added to 60 mL of the mixed solution and stirred, and the mixture was reacted at 200°C for 12 h. After the reaction was completed, the precipitate was collected, washed, and dried to obtain glycerol titanium microrods;

[0073] (2) Disperse 0.2 g of titanium glycerate microrods into 55 mL of anhydrous ethanol, add 1 mmol of ferric nitrate nonahydrate, and stir until the anhydrous ethanol is completely evaporated to obtain iron salt / titanium glycerate microrods;

[0074] (3) placing the iron salt / titanium glycerate microrods in a muffle furnace and heating the temperature to 300°C at a heating rate of 2°C / min, and keeping the temperature for 4 hours to obtain ferric oxide / titanium dioxide microrods;

[0075] (4) After mixing 0.1 g of ferric oxide / titanium dioxide microrods with 0.1 g of sulfur powder to obtain a mixture, the mixture was placed in a tubular furnace, heated to 600 °C at a heating rate of 2 °C / min under an argon atmosphere, and kept warm for 1 h to obtain an iron disulfide / titanium dioxide microrod composite material.

[0076] Example 6: Preparation of Iron Disulfide / Titanium Dioxide Microrod Composite Material

[0077] (1) Ethylene glycol and glycerol were mixed in a volume ratio of 8:1 to obtain a mixed solution, 5 mmol of titanium isopropoxide was added to 60 mL of the mixed solution with stirring, and the mixture was reacted at 120° C. for 10 h. After the reaction was completed, the precipitate was collected, washed, and dried to obtain titanium glycerate microrods;

[0078] (2) Disperse 0.2 g of titanium glycerate microrods into 30 mL of anhydrous ethanol, add 3 mmol of ferric nitrate nonahydrate, and stir until the anhydrous ethanol is completely evaporated to obtain iron salt / titanium glycerate microrods;

[0079] (3) placing the iron salt / titanium glycerate microrods in a muffle furnace and heating the temperature to 600°C at a heating rate of 10°C / min, and keeping the temperature for 0.5 h to obtain ferric oxide / titanium dioxide microrods;

[0080] (4) After mixing 0.1 g of ferric oxide / titanium dioxide microrods with 0.5 g of sulfur powder to obtain a mixture, the mixture was placed in a tubular furnace, heated to 400 °C at a heating rate of 10 °C / min under an argon atmosphere, and kept warm for 4 h to obtain an iron disulfide / titanium dioxide microrod composite material.

[0081] Comparative Example 1: Preparation of Iron Disulfide / Titanium Dioxide Microrod Composite Material

[0082] The difference between this comparative example and Example 4 is that in step (2), 0.2 g of titanium glycerate microrods and 2 mmol of ferric nitrate nonahydrate are mixed by ball milling to obtain iron salt / titanium glycerate microrods.

[0083] Test Example 1: Electrochemical Performance

[0084] The iron disulfide / titanium dioxide microrod composite material prepared in Example 4 and Comparative Example 1 was used as the negative electrode of the potassium ion battery to test the electrochemical cycle stability and rate performance of the potassium ion battery. The results are as follows: Figure 3-Figure 4 shown.

[0085] Among them, during the cycle stability performance test, the charge and discharge current density was 0.1A / g, and the end charge and discharge voltage was 0.01-3V; during the rate performance test, the charge and discharge current density was 0.1, 0.2, 0.5, 1, 2, 5, and 0.1A / g, respectively, and the end charge and discharge voltage was 0.01-3V.

[0086] The specific steps are as follows: the iron disulfide / titanium dioxide microrod composite material, acetylene black and potassium carboxymethyl cellulose prepared in Example 4 and Comparative Example 1 are added to deionized water in a mass ratio of 8:1:1, stirred evenly, and then coated on a 25 μm thick copper foil, and then the copper foil is placed in a vacuum drying oven at 80°C and dried for 12 hours. The copper foil is taken out and cut into discs with a diameter of 16 mm as negative electrode sheets by a cutting machine, and then the prepared negative electrode sheets are directly assembled with metallic potassium as counter electrodes into button batteries to measure their electrochemical properties, wherein the electrolyte is 0.8M KPF6 / DEC:EC (1:1, volume ratio).

[0087] Depend on Figure 3 It can be seen that the iron disulfide / titanium dioxide microrod composite material prepared in Example 4 exhibits excellent cycle stability as a potassium ion negative electrode material, and the reversible specific capacity is maintained at 544.9 mAh / g after 100 cycles, and its capacity retention rate is as high as 89.9%, while the iron disulfide / titanium dioxide microrod composite material prepared in Comparative Example 1 is used as a potassium ion negative electrode material. After 100 cycles, the reversible specific capacity is 17.8 mAh / g, and the capacity retention rate is only 3.1%. It can be seen that the iron disulfide nanoparticles prepared by the present invention are uniformly dispersed on the microrods assembled by the titanium dioxide nanosheets, which can effectively alleviate the volume change of iron disulfide during the de- / embedded potassium ions, while the iron disulfide / titanium dioxide microrod composite material prepared by mechanical ball milling in Comparative Example 1 causes the agglomeration of nanoparticles due to the uneven dispersion of iron disulfide and the uneven particle size, resulting in rapid attenuation of electrochemical performance.

[0088] Depend on Figure 4It can be seen that the iron disulfide / titanium dioxide microrod composite material prepared in Example 4 of the present invention, when used as a potassium ion negative electrode material, also exhibits excellent rate performance. When the charge and discharge current increases to 5.0 A / g, it still maintains a high reversible specific capacity of 422.4 mAh / g, while the iron disulfide / titanium dioxide microrod composite material prepared in Comparative Example 1 is used as a potassium ion negative electrode material. When the charge and discharge current increases to 5.0 A / g, the reversible specific capacity is only 3.9 mAh / g. It can be seen that the present invention causes iron salts to recrystallize on the surface of glyceric acid titanium nanosheets by ethanol volatilization. Compared with the physical mixing of ball milling, it not only improves the uniformity of component distribution in the composite material, but also makes the iron disulfide particle size more uniform. The present invention utilizes the pores formed by the cross-intersection of the small particle size of iron disulfide and the titanium dioxide nanosheets that effectively increase the contact area between the composite material and the electrolyte, shortens the diffusion path of potassium ions, and thus improves the rate performance of the overall composite material.

[0089] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing an iron disulfide / titanium dioxide microrod composite material, characterized in that: The steps include: (1) Ethylene glycol and glycerol are mixed to obtain a mixed solution, a titanium source is added to the mixed solution for reaction, and after the reaction is completed, a precipitate is collected, washed, and dried to obtain glyceric acid titanium microrods; (2) dispersing titanium glycerate microrods in anhydrous ethanol, adding iron salt, and stirring until the anhydrous ethanol is completely evaporated to obtain iron salt / titanium glycerate microrods; (3) heat treating the iron salt / titanium glycerate microrods to obtain iron oxide / titanium dioxide microrods; (4) The ferric oxide / titanium dioxide microrods are mixed with sulfur powder to obtain a mixture, and the mixture is heat treated to obtain an ferric disulfide / titanium dioxide microrod composite material.

2. The method for preparing the iron disulfide / titanium dioxide microrod composite material according to claim 1, characterized in that: In step (1), in the mixed solution, the volume ratio of ethylene glycol to glycerol is (3-8):1; the material-liquid ratio of the titanium source to the mixed solution is (1-5) mmol:60 mL.

3. The method for preparing the iron disulfide / titanium dioxide microrod composite material according to claim 1, characterized in that: In step (1), the titanium source is one of titanyl sulfate, tetrabutyl titanate, titanium tetrachloride, and titanium isopropoxide.

4. The method for preparing the iron disulfide / titanium dioxide microrod composite material according to claim 1, characterized in that: In step (1), the reaction temperature is 120-200°C and the reaction time is 10-18h.

5. The method for preparing the iron disulfide / titanium dioxide microrod composite material according to claim 1, characterized in that: In step (2), the iron salt is one of ferric nitrate nonahydrate, ferric carbonate, ferrocene, ferric sulfate, and ferric sulfate heptahydrate.

6. The method for preparing the iron disulfide / titanium dioxide microrod composite material according to claim 1, characterized in that: In step (2), the ratio of the added amount of titanium glycerate microrods and iron salt is 0.2 g: (1-3) mmol; the solid-liquid ratio of titanium glycerate microrods and anhydrous ethanol is 0.2 g: (30-60) mL.

7. The method for preparing the iron disulfide / titanium dioxide microrod composite material according to claim 1, characterized in that: In step (3), the heat treatment conditions are: heating to 300-600°C at a heating rate of 2-10°C / min, and keeping the temperature for 0.5-4h.

8. The method for preparing the iron disulfide / titanium dioxide microrod composite material according to claim 1, characterized in that: In step (4), the mass ratio of ferric oxide / titanium dioxide microrods to sulfur powder is 1:(1-10); the heat treatment operation is: placing the mixture in an argon atmosphere, heating it to 400-600°C at a heating rate of 2-10°C / min, and keeping it warm for 1-4h.

9. The iron disulfide / titanium dioxide microrod composite material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The iron disulfide / titanium dioxide microrod composite material is composed of titanium dioxide microrods and iron disulfide nanoparticles. The iron disulfide nanoparticles are dispersed on the surface of the titanium dioxide microrods. The titanium dioxide microrods are composed of crossed titanium dioxide nanosheets. The size of the iron disulfide nanoparticles is 15-40nm, and the thickness of the titanium dioxide nanosheets is 40-80nm.

10. Use of the iron disulfide / titanium dioxide microrod composite material according to claim 9 in preparing anode materials for potassium ion batteries.

Citation Information

Patent Citations

  • Pyrite iron disulfide / titanium dioxide composite material as well as preparation method and application thereof

    CN113578351A

  • MOS2 (molybdenum disulfide) and TiO2 (titanium dioxide) nanocomposites and production method thereof

    CN103426648A

  • Titanium dioxide-iron disulfide core-shell structure material and preparation method thereof

    CN105336951A

  • Preparation method of molybdenum sulfide-titanium oxide nanocomposite material, and application of preparation method

    CN109580746A

  • Visible-light-induced photocatalyst and preparation method and application thereof

    CN112138684A